The Relationship Between Job Characteristics And Job Satisfaction Toward Affective Commitment: The Case Of Engineers In Sepakat Setia Perunding Sdn Bhd. - Wong, Siew Lee (2010)

(untitled)
Komitmen Organisasi telah dikaji dengan meluas sebagai satu factor penting dalam pengekalan dan motivasi pekerja.